Dual career: dilemmas between sport and school - Melo, Leonardo Bernardes Silva de; Rocha, Hugo Paula Almeida da; Romão, Marcio Gabriel; dos Santos, Wagner; Soares, Antonio Jorge Gonçalves (Journal of Physical Education (Maringá), 2020)
This article discusses the models for the reconciliation of career, sports and school routines in the Federal Government Athletic Scholarship Program, with students-contemplators and results obtained in 2011. Characterization as a quantitative research carried out by means of a closed questionnaire invested in 131 athletes of the modalities of athletics, judo and swimming, being 64 female and 67 male. They show the following results: 1) as different sports modalities; 2) initiation process in the temporary variables of the forms of investment; 3) lower schooling of parents and athletes in athletics, as well as lower social class. In the face of the obstacles of the dual career, athletes, clubs, schools and families are adopting tactics of conciliation and even mockery of programs to support sports training.